In vitro analysis of chemotactic leukocyte migration in 3D environments - Sixt, Michael K; Lämmermann, Tim (Cell Migration)
Cell migration on two-dimensional (2D) substrates follows entirely different rules than cell migration in three-dimensional (3D) environments. This is especially relevant for leukocytes that are able to migrate in the absence of adhesion receptors within the confined geometry of artificial 3D extracellular matrix scaffolds and within the interstitial space in vivo. Here, we describe in detail a simple and economical protocol to visualize dendritic cell migration in 3D collagen scaffolds along chemotactic gradients. This method can be adapted to other cell types and may serve as a physiologically relevant paradigm for the directed locomotion of most amoeboid cells.

Structure-based design of light-controlled proteins - Harald Janovjak; Isacoff, Ehud Y (Photosensitive Molecules for the Control of Biological Function)
Small photochromic molecules are widespread in nature and serve as switches for a plethora of light-controlled processes. In a typical photoreceptor, the different geometries and polarities of the photochrome isomers are tightly coupled to functionally relevant conformational changes in the proteins. The past decade has seen extensive efforts to mimic nature and create proteins controlled by synthetic photochromes in the laboratory. Here, we discuss the role of molecular modeling to gain a structural understanding of photochromes and to design light-controlled peptides and proteins. We address several fundamental questions: What are the molecular structures of photochromes, particularly for metastable isomers that cannot be addressed experimentally? How are the structures of bistable photoisomers coupled to the conformational states of peptides and proteins? Can we design light-controlled proteins rapidly and reliably? After an introduction to the principles of molecular modeling, we answer these questions by examining systems that range from the size of isolated photochromes, to that of peptides and large cell surface receptors, each from its unique computational perspective.

The Amazon River system as an ecological barrier driving genetic differentiation of the pink dolphin (Inia geoffrensis) - Hollatz, Claudia; Vilaça, Sibelle; Fernandes Redondo, Rodrigo A; Marmontel, Míriam; Baker, Cyndi; Santos, Fabrício (Biological Journal of the Linnean Society)
The pink dolphin (Inia geoffrensis) is widely distributed along the Amazon and Orinoco basins, covering an area of approximately 7 million km2. Previous morphological and genetic studies have proposed the existence of at least two evolutionary significant units: one distributed across the Orinoco and Amazon basins and another confined to the Bolivian Amazon. The presence of barriers in the riverine environment has been suggested to play a significant role in shaping present-day patterns of ecological and genetic structure for this species. In the present study, we examined the phylogeographic structure, lineage divergence time and historical demography using mitochondrial (mt)DNA sequences in different pink dolphin populations distributed in large and small spatial scales, including two neighbouring Brazilian Amazon populations. mtDNA control region (CR) analysis revealed that the Brazilian haplotypes occupy an intermediate position compared to three previously studied geographic locations: the Colombian Amazon, the Colombian Orinoco, and the Bolivian Amazon. On a local scale, we have identified a pattern of maternal isolation between two neighbouring populations from Brazil. Six mtDNA CR haplotypes were identified in Brazil with no sharing between the two populations, as well as specific cytochrome b (cyt b) haplotypes identified in each locality. In addition, we analyzed autosomal microsatellites to investigate male-mediated gene flow and demographic changes within the study area in Brazil. Data analysis of 14 microsatellite loci failed to detect significant population subdivision, suggesting that male-mediated gene flow may maintain homogeneity between these two locations. Moreover, both mtDNA and microsatellite data indicate a major demographic collapse within Brazil in the late Pleistocene. Bayesian skyline plots (BSP) of mtDNA data revealed a stable population for Colombian and Brazilian Amazon lineages through time, whereas a population decline was demonstrated in the Colombian Orinoco lineage. Moreover, BSP and Tajima's D and Fu's Fs tests revealed a recent population expansion exclusively in the Bolivian sample. Finally, we estimated that the diversification of the Inia sp. lineage began in the Late Pliocene (approximately 3.1 Mya) and continued throughout the Pleistocene.

Patterns of diversification in two species of short-tailed bats (Carollia Gray, 1838): the effects of historical fragmentation of Brazilian rainforests. - Pavan, Ana; Martins, Felipe; Santos, Fabrício; Ditchfield, Albert; Fernandes Redondo, Rodrigo A (Biological Journal of the Linnean Society)
The small-sized frugivorous bat Carollia perspicillata is an understory specialist and occurs in a wide range of lowland habitats, tending to be more common in tropical dry or moist forests of South and Central America. Its sister species, Carollia brevicauda, occurs almost exclusively in the Amazon rainforest. A recent phylogeographic study proposed a hypothesis of origin and subsequent diversification for C. perspicillata along the Atlantic coastal forest of Brazil. Additionally, it also found two allopatric clades for C. brevicauda separated by the Amazon Basin. We used cytochrome b gene sequences and a more extensive sampling to test hypotheses related to the origin and diversification of C. perspicillata plus C. brevicauda clade in South America. The results obtained indicate that there are two sympatric evolutionary lineages within each species. In C. perspicillata, one lineage is limited to the Southern Atlantic Forest, whereas the other is widely distributed. Coalescent analysis points to a simultaneous origin for C. perspicillata and C. brevicauda, although no place for the diversification of each species can be firmly suggested. The phylogeographic pattern shown by C. perspicillata is also congruent with the Pleistocene refugia hypothesis as a likely vicariant phenomenon shaping the present distribution of its intraspecific lineages.

Estimating linkage disequilibria - Barton, Nicholas H (Heredity)

The difference in length of curves in R^n - Fasy, Brittany Terese (Acta Sci. Math. (Szeged))
We bound the difference in length of two curves in terms of their total curvatures and the Fréchet distance. The bound is independent of the dimension of the ambient Euclidean space, it improves upon a bound by Cohen-Steiner and Edelsbrunner, and it generalizes a result by Fáry and Chakerian.

Scyllarus arctus (Crustacea: Decapoda: Scyllaridae) final stage phyllosoma identified by DNA analysis, with morphological description - Palero, Ferran; Guerao, Guillermo; Clark, Paul; Abello, Pere (Journal of the Marine Biological Association of the United Kingdom)
Advanced stages of Scyllarus phyllosoma larvae were collected by demersal trawling during fishery research surveys in the western Mediterranean Sea in 2003–2005. Nucleotide sequence analysis of the mitochondrial 16S rDNA gene allowed the final-stage phyllosoma of Scyllarus arctus to be identified among these larvae. Its morphology is described and illustrated. This constitutes the second complete description of a Scyllaridae phyllosoma with its specific identity being validated by molecular techniques (the first was S. pygmaeus). These results also solved a long lasting taxonomic anomaly of several species assigned to the ancient genus Phyllosoma Leach, 1814. Detailed examination indicated that the final-stage phyllosoma of S. arctus shows closer affinities with the American scyllarid Scyllarus depressus or with the Australian Scyllarus sp. b (sensu Phillips et al., 1981) than to its sympatric species S. pygmaeus.

Cell sorting in development - Krens, Gabriel; Heisenberg, Carl-Philipp J (Forces and Tension in Development)
During the development of multicellular organisms, cell fate specification is followed by the sorting of different cell types into distinct domains from where the different tissues and organs are formed. Cell sorting involves both the segregation of a mixed population of cells with different fates and properties into distinct domains, and the active maintenance of their segregated state. Because of its biological importance and apparent resemblance to fluid segregation in physics, cell sorting was extensively studied by both biologists and physicists over the last decades. Different theories were developed that try to explain cell sorting on the basis of the physical properties of the constituent cells. However, only recently the molecular and cellular mechanisms that control the physical properties driving cell sorting, have begun to be unraveled. In this review, we will provide an overview of different cell-sorting processes in development and discuss how these processes can be explained by the different sorting theories, and how these theories in turn can be connected to the molecular and cellular mechanisms driving these processes.

Covering and packing with spheres by diagonal distortion in R^n - Edelsbrunner, Herbert; Kerber, Michael (Rainbow of Computer Science)
We address the problem of covering ℝ n with congruent balls, while minimizing the number of balls that contain an average point. Considering the 1-parameter family of lattices defined by stretching or compressing the integer grid in diagonal direction, we give a closed formula for the covering density that depends on the distortion parameter. We observe that our family contains the thinnest lattice coverings in dimensions 2 to 5. We also consider the problem of packing congruent balls in ℝ n , for which we give a closed formula for the packing density as well. Again we observe that our family contains optimal configurations, this time densest packings in dimensions 2 and 3.

STM imaging of a bound state along a step on the surface of the topological insulator Bi2Te3 - Alpichshev, Zhanybek; Analytis, J G; Chu, J H; Fisher, I R; Kapitulnik, A (Physical Review B - Condensed Matter and Materials Physics)
We present a detailed study of the local density of states (LDOS) associated with the surface-state band near a step edge of the strong topological insulator Bi2Te3 and reveal a one-dimensional bound state that runs parallel to the step edge and is bound to it at some characteristic distance. This bound state is clearly observed in the bulk gap region, while it becomes entangled with the oscillations of the warped surface band at high energy, and with the valence-band states near the Dirac point. We obtain excellent fits to theoretical predictions [Alpichshev, 2011] that properly incorporate the three-dimensional nature of the problem to the surface state. Fitting the data at different energies, we can recalculate the LDOS originating from the Dirac band without the contribution of the bulk bands or incoherent tunneling effects.

Computing elevation maxima by searching the Gauss sphere - Wang, Bei; Edelsbrunner, Herbert; Morozov, Dmitriy (Journal of Experimental Algorithmics)
The elevation function on a smoothly embedded 2-manifold in R-3 reflects the multiscale topography of cavities and protrusions as local maxima. The function has been useful in identifying coarse docking configurations for protein pairs. Transporting the concept from the smooth to the piecewise linear category, this paper describes an algorithm for finding all local maxima. While its worst-case running time is the same as of the algorithm used in prior work, its performance in practice is orders of magnitudes superior. We cast light on this improvement by relating the running time to the total absolute Gaussian curvature of the 2-manifold.

Specific heat of a ferroelectric PZT ceramic at the morphotropic phase boundary - Lang, S. B.; Lashley, J. C.; Modic, Kimberly A; Fisher, R. A.; Zhu, W. M.; Ye, Z. G. (Proceedings of the 2010 IEEE International Conference on Solid Dielectrics)
Ferroelectric ceramic materials have a wide range of applications because of their piezoelectric and pyroelectric properties. One of their most important physical properties is the specific heat. In this study, the specific heats of a series of lead-zirconate-titanate (PZT) compositions in the vicinity of the morphotropic phase boundary (MPB) were measured. The temperature range was from 1.8 to 300 K. It is believed that these are the lowest temperature measurements ever made on PZT. Differences between the specific heats of the different compositions were very small. However, the calculated Debye temperatures were slightly different. The results are useful in computing design parameters for technical devices.

Specific heat of a ferroelectric PZT ceramic at the morphotropic phase boundary - Lang, S.B.; Lashley, J.C.; Modic, Kimberly A; Fisher, R.A.; Zhu, W.M.; Ye, Z.G. (15th IEEE Mediterranean Electrotechnical Conference)
Ferroelectric ceramic materials have a wide range of applications because of their piezoelectric and pyroelectric properties. One of their most important physical properties is the specific heat. In this study, the specific heats of a series of lead-zirconate-titanate (PZT) compositions in the vicinity of the morphotropic phase boundary (MPB) were measured. The temperature range was from 1.8 to 300 K. It is believed that these are the lowest temperature measurements ever made on PZT. Differences between the specific heats of the different compositions were very small. However, the calculated Debye temperatures were slightly different. The results are useful in computing design parameters for technical devices.

Online stochastic packing applied to display ad allocation - Feldman, Jon; Henzinger, Monika H; Korula, Nitish; Mirrokni, Vahab S.; Stein, Cliff (18th Annual European Symposium on Algorithms)
Inspired by online ad allocation, we study online stochastic packing integer programs from theoretical and practical standpoints. We first present a near-optimal online algorithm for a general class of packing integer programs which model various online resource allocation problems including online variants of routing, ad allocations, generalized assignment, and combinatorial auctions. As our main theoretical result, we prove that a simple dual training-based algorithm achieves a (1 − o(1))-approximation guarantee in the random order stochastic model. This is a significant improvement over logarithmic or constant-factor approximations for the adversarial variants of the same problems (e.g. factor 1−1𝑒 for online ad allocation, and log(m) for online routing). We then focus on the online display ad allocation problem and study the efficiency and fairness of various training-based and online allocation algorithms on data sets collected from real-life display ad allocation system. Our experimental evaluation confirms the effectiveness of training-based algorithms on real data sets, and also indicates an intrinsic trade-off between fairness and efficiency.

Mechanisms for the marriage and the assignment game - Dütting, Paul; Henzinger, Monika H (7th International Conference on Algorithms and Complexity)
Starting with two models fifty years ago, the discrete marriage game [1] and the continuous assignment game [2], the study of stable matchings has evolved into a rich theory with applications in many areas. Most notably, it has lead to a number of truthful mechanisms that have seen a recent rejuvenation in the context of sponsored search. In this paper we survey the history of these problems and provide several links to ongoing research in the field.

Sponsored search, market equilibria, and the Hungarian Method - Dütting, Paul; Henzinger, Monika H; Weber, Ingmar (27th International Symposium on Theoretical Aspects of Computer Science)
Two-sided matching markets play a prominent role in economic theory. A prime example of such a market is the sponsored search market where $n$ advertisers compete for the assignment of one of $k$ sponsored search results, also known as ``slots'', for certain keywords they are interested in. Here, as in other markets of that kind, market equilibria correspond to stable matchings. In this paper, we show how to modify Kuhn's Hungarian Method (Kuhn, 1955) so that it finds an optimal stable matching between advertisers and advertising slots in settings with generalized linear utilities, per-bidder-item reserve prices, and per-bidder-item maximum prices. The only algorithm for this problem presented so far (Aggarwal et al., 2009) requires the market to be in ''general position''. We do not make this assumption.

How much is your personal recommendation worth? - Dütting, Paul; Henzinger, Monika H; Weber, Ingmar (Proceedings of the 19th international conference on World wide web)
Suppose you buy a new laptop and, simply because you like it so much, you recommend it to friends, encouraging them to purchase it as well. What would be an adequate price for the vendor of the laptop to pay for your recommendation? Personal recommendations like this are of considerable commercial interest, but unlike in sponsored search auctions there can be no truthful prices. Despite this "lack of truthfulness" the vendor of the product might still decide to pay you for recommendation e.g. because she wants to (i) provide you with an additional incentive to actually recommend her or to (ii) increase your satisfaction and/or brand loyalty. This leads us to investigate a pricing scheme based on the Shapley value [5] that satisfies certain "axioms of fairness". We find that it is vulnerable to manipulations and show how to overcome these difficulties using the anonymity-proof Shapley value of [4].

The stability of the h-index - Henzinger, Monika H; Suñol, Jacob; Weber, Ingmar (Scientometrics)
Over the last years the h-index has gained popularity as a measure for comparing the impact of scientists. We investigate if ranking according to the h-index is stable with respect to (i) different choices of citation databases, (ii) normalizing citation counts by the number of authors or by removing self-citations, (iii) small amounts of noise created by randomly removing citations or publications and (iv) small changes in the definition of the index. In experiments for 5,283 computer scientists and 1,354 physicists we show that although the ranking of the h-index is stable under most of these changes, it is unstable when different databases are used. Therefore, comparisons based on the h-index should only be trusted when the rankings of multiple citation databases agree.

Novel sensitive determination of steryl glycosides in biodiesel by gas chromatography-mass spectroscopy - Pieber, Bartholomäus; Schober, Sigurd; Goebl, Christoph; Mittelbach, Martin (Journal of Chromatography A)
A new method was developed for the quantitative analysis of steryl glycosides in biodiesel (fatty acid methyl esters). This method is much more sensitive than existing methods and has minimum limits of quantification of 50 μg/kg, compared to previously published minimum limits of quantification of about 15 mg/kg. The analysis is based on gas chromatography–mass spectroscopy determination of simple pre-treated and silylated samples via single ion monitoring at 147, 204, 217 m/z, which are specific ions for the silylated sugar moiety. Quantification was carried out using cholesteryl β-d-glucopyranoside as internal standard. The modified synthesis and purification of the internal standard is also presented as well as the characterization by NMR and mass spectroscopy. The advantage of the method compared with other approaches is the simplified sample preparation avoiding extra pre-treatment steps coupled with complete derivatization of the sugar hydroxyl groups by using N,O-bis(trimethylsilyl)acetamide with 5% trimethylchlorosilane as derivatization reagent. On the given conditions high recovery rates ≥89% can be obtained. Evaluation of lab specific variance and intermediate precision underline the robustness of the method which will be further assessed by Round robin tests.

Tapetal cell fate, lineage and proliferation in the Arabidopsis anther - Feng, Xiaoqi; Dickinson, Hugh G. (Development)
The four microsporangia of the flowering plant anther develop from archesporial cells in the L2 of the primordium. Within each microsporangium, developing microsporocytes are surrounded by concentric monolayers of tapetal, middle layer and endothecial cells. How this intricate array of tissues, each containing relatively few cells, is established in an organ possessing no formal meristems is poorly understood. We describe here the pivotal role of the LRR receptor kinase EXCESS MICROSPOROCYTES 1 (EMS1) in forming the monolayer of tapetal nurse cells in Arabidopsis. Unusually for plants, tapetal cells are specified very early in development, and are subsequently stimulated to proliferate by a receptor-like kinase (RLK) complex that includes EMS1. Mutations in members of this EMS1 signalling complex and its putative ligand result in male-sterile plants in which tapetal initials fail to proliferate. Surprisingly, these cells continue to develop, isolated at the locular periphery. Mutant and wild-type microsporangia expand at similar rates and the ‘tapetal’ space at the periphery of mutant locules becomes occupied by microsporocytes. However, induction of late expression of EMS1 in the few tapetal initials in ems1 plants results in their proliferation to generate a functional tapetum, and this proliferation suppresses microsporocyte number. Our experiments also show that integrity of the tapetal monolayer is crucial for the maintenance of the polarity of divisions within it. This unexpected autonomy of the tapetal ‘lineage’ is discussed in the context of tissue development in complex plant organs, where constancy in size, shape and cell number is crucial.
Keywords: Developmental Biology; Molecular Biology; Anther Tapetum; Arabidopsis; Cell Fate Establishment; EMS1; Reproductive Cell Lineage